Professional commitment mediates the effects of discipline, environment, and motivation on employee performance at Indonesia’s Ministry of Agriculture - Dian Riskarini; Lies Putriana; Roy Prakoso; Sharla Martiza (Goodwood Publishing, 2025)
Purpose: This study aims to analyze the direct influence of work discipline, work environment, and work motivation on employee performance at the Secretariat of the Directorate General of Plantations, Ministry of Agriculture of the Republic of Indonesia, and the indirect effect through professional commitment as a mediating variable. Research Methodology: The research employs a quantitative method with a mixed design approach combining both verification and descriptive research. Data were collected using a questionnaire distributed to 155 employees at the Secretariat of the Directorate General of Plantations, Ministry of Agriculture. Data analysis was conducted using Multiple Linear Regression Analysis and Path Analysis with Structural Equation Modeling (SEM) PLS software. Results: The results indicate that work discipline, work environment, and work motivation have a significant impact on employee performance, both directly and indirectly through professional commitment as a mediator. Conclusions: The study concludes that improving work discipline, work environment, work motivation, and professional commitment can enhance employee performance in the public sector, particularly within the Secretariat of the Directorate General of Plantations. Limitations: The research is limited to employees of the Secretariat of the Directorate General of Plantations and does not consider other external variables that may influence employee performance. Contribution: This study provides practical guidance for improving employee performance in the public sector through a holistic approach that includes work discipline, work environment, work motivation, and professional commitment. Additionally, the conceptual model developed can be applied to similar institutions.